(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with urinary tract infections (UTIs) and analyze some factors related to urine culture results. Subjects and Methods: A cross-sectional descriptive study was conducted on 52 patients diagnosed with UTI at the Department of Nephrology – Urology and Hemodialysis, Thai Nguyen National Hospital, from January 2025 to October 2025. Related factors were analyzed using the Chi-square test, calculating Odds Ratio (OR) with a 95% confidence interval; p<0.05 was considered statistically significant. Results: Females accounted for 76.92%. Common symptoms included dysuria (73.08%), urinary frequency (61.54%), and flank pain (51.92%). Positive leukocyturia was found in 78.85%, elevated CRP in 63.46%, and positive urinary nitrite in 42.31%. E.coli was the most common pathogen (67.86%). Among E. coli isolates, the resistance rate was 89.5% to cefazolin and 68.4% to ciprofloxacin; 73.7% to cefotaxime and 84.2% to trimethoprim/sulfamethoxazole. Analysis showed that urine culture results were significantly associated with urinary nitrite (OR=5.873; 95% CI: 1.694–20.36; p=0.004), CRP (OR=4.333; 95% CI: 1.295–14.505; p=0.015), and abnormalities on urinary tract ultrasound (OR=8.022; 95% CI: 2.265–28.415; p=0.001). Conclusion: E.coli is the main causative agent of UTIs. Urinary nitrite, CRP, and abnormalities on urinary tract ultrasound are associated with urine culture results, contributing to diagnostic orientation and appropriate treatment strategy selection.